Atlantic cod growth model: Open source Python package for numerical growth experiments - Nadezhda Sokolova; Anja Rohner; Martin Butzin; Hans-Otto Pörtner; Gerrit Lohmann (SoftwareX)
In this article we introduce an open source tool that is used to study growth of Atlantic cod (Gadus morhua), an economically important fish species, in different temperature environments. It is a mechanistic physiology-based growth model that simulates growth in controlled laboratory experiments as well as in an open sea environment. The model can be used by universities, industrial, and research institutes as a tool for testing research hypotheses, and studying temperature-dependent growth in fishes.